BOTANICAL ELIXIRS: A RARE CASE OF SUICIDAL POISONING WITH A FLOWER STIMULANT - Das, Siddhartha; Anil, Arya K; Badhe, Bhawana A; Devarajan, Shanmugam; Vikram, S (Journal of Forensic Medicine and Toxicology, 2025)
Nitrobenzene-based flowering stimulants are rare causes of fatal poisoning. This case highlights acute methemoglobinemia due to ingestion of a stimulant, describing clinical, autopsy, and toxicological findings.